Research for Extant Analogs for Early Land Plant Algal Progenitors - Gontarek, Bryan (My University, 2011)
The aquatic algal ancestors that gave rise to the earliest terrestrial plants are not normally expected to have left much in the way of fossil remains. The one possible exception to this is the dispersal bodies (spores). This study analyzed those with evidence of possible resistant cells to acetolysis to see if recognizable remains survived. The remaining cells were then analyzed with scanning electron microscopy (SEM) and transmission electron microscopy (TEM).
Color poster with text, images, and charts.
Keywords: Algal communities; Fossils--United States; Plants--Evolution; Posters